Explicit analytic solution for heat and mass transfer in a desiccant wheel using a simplified model. (15th December 2015) - Kang, Hyungmook; Lee, Gilbong; Lee, Dae-Young
Abstract: Heat and mass transfer in a desiccant wheel was modeled into a set of linear differential equations under the linearization assumptions on the temperature and humidity profiles and the psychrometric relation. The explicit analytic solutions to the temperature and humidity ratio of the outlet air were obtained using the simplified model and assessed for the validity by comparison with a numerical simulation at the range of low regeneration temperatures. The RMS (Root Mean Square) errors were evaluated less than 10% for most operation range of the air velocity, the dehumidification period and the psychrometric conditions of the regeneration air. The analysis revealed that the behavior of a desiccant wheel depends on four major dimensionless parameters: κ, σ, N, and ψ, each of which represents the sorption capacity, the thermal capacity, the transfer capacity of the wheel and the psychrometric relation of the air, respectively. The psychrometric progress of the outlet air was observed to be divided into two distinct phases, each dominated by an exponential function identified by the four parameters. Asymptotic analysis on the solutions showed that the early phase is governed by the thermal characteristics while the later phase is by the sorption characteristics of the desiccant wheel. Highlights: A simplified model was devised for heat and mass transfer in a desiccant wheel. Explicit analytic solution to the simplified model was obtained. The analytic solution was verified by comparison with numerical simulations. 4 characteristic parameters were derived identifying the process in the wheel. The psychrometric progress was shown to be divided into two distinct phases.